The Introduction of English-Induced Neologisms in Spanish Tweets: A Case-Study on covidiota - Kailich, Franziska (Frontiers in Communication, 2022)
This paper intends to trace the introduction of an English-induced, COVID-related neologism, covidiota, into the Spanish language. The study is based on a corpus of tweets, starting in March 2020. It examines several specific features which mark the word as a new, unfamiliar item, such as different ways of graphical highlighting, for example. On the other hand, the paper aims to detect possible indicators of an integration of covidiota into the Spanish language use in the tweet corpus compiled for this case study.